Optimization of optimum condition for phytic acid extraction from rice bran - Saad, Norazalina; Mohd Esa, Norhaizan; Ithnin, Hairuszah; Shafie, Nurul Husna (Academic Journals, 2011)
Phytic acid is one of the bioactive compounds that are being intensively studied to evaluate their effects on health. This study was carried out to determine the optimum condition for phytic acid extraction from rice bran. Three main parameters were considered to optimize the condition for phytic acid extraction; different types of extracting solvent, length of extraction time and influence of different pH adjustment. Three acidic solutions were selected and were trichloroacetic acid (TCA), hydrochloric acid (HCl) and sulphuric acid (H2SO4). The results showed that 5% of H2SO4 in pH 0.6 and after 30 min of extraction time gave the highest amount of phytic acid compared to 10% of TCA and 3% of HCl. The content of phytic acid in rice bran ranged from 0.22 to 2.22% for the different parameters optimized. Different methods produced different content of phytic acid from rice bran. Therefore, 5% of H2SO4 in pH 0.6 and 30 min of extraction time was the best condition for the optimum production of phytic acid.